Fenomena Multikulturalisme dalam Sejarah Islam Klasik - Dudung Abdurahman (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2016)
Multiculturalism today become an issue and study materials are attractive for a wide range of knowledge about pluralism in the social order, including in relation to the lives of muslims. This study examines the relationship between Islam and multiculturalism, based on the premise that Islam as a system of doctrine that comes from God's revelation is always growing and developing appropriate socio-cultural context of its adherents, as shown in the history of the classical period. Therefore, the main problem of this study, how the life of multiculturalism in muslim society in that period. So the study aims to map patterns of multiculturalism within the Muslim communities. The research was developed by the historical method, with socio-cultural approach. Based on this study found patterns of multiculturalism as follows: First, the muslim community during the period of the Prophet and the Khulafa al-Rashidun-based Arab culture, and Islam is growing with the development pattern of teaching that accommodate the cultural forms that are rooted in the tradition of al-qabaliyyah al'ashabiyyah. Second, the pattern of growing muslim community in the politics of Arabism, as at the time of the Umayyad Daula, acculturation would encourage the growth of the Muslim-Arab Muslim communities against non-Arabs to the expansion of Islam during this time. Third, multiculturalism patterns more apparent as the reality of pluralism in Muslim society is indicated by the role of communities in the context of non-Arab Islamic culture and civilization construction, as developed Abbasid.